ADSORPSI LOGAM Ag(I) DAN Ni(II) PADA HIBRIDA AMINO-SILIKA DARI ABU SEKAM PADI - Limatahu, Nur Asbirayani (Green Earth, 2012)
The research of Amino-silica hybrid(ASH) through process of sol-gel by using compound (3-aminopropyl)-trimetokxysilane(APS) from natrium silicate result processing of rice hull ash adsorption of metal Ag(I) and Ni(II).ASH was prepared out by adding HCl 3 M solution to the mixture of natrium silicate solution and (3-aminopropyl)-trimetokxysilane. The produced adsorbent was characterized by X-ray diffraction (XRD) and infrared spectrophotometer (FTIR). Adsorption of metal, was carried out in batch technique (static system). The adsorbed metal ions was quantitatively calculated as difference of ion concentration in metal solution before and after adsorption based on the AAS analyses Key words : rice hull ash, amino-silica hybrid, adsorption